Apresentação, discussão e realização de três técnicas estendidas na obra Solus, para trompete desacompanhado, de Stanley Friedman - Nascimento, Vinícius Côrtes do (2019)
Stanley Friedman's Solus composition, composed in 1975, is inserted in the repertoire of the 20th century solo trumpet, the piece is divided into four movements, Introduction, Furtively, Scherzando and Waltz and Fanfarre. In the work is remarkable a timbre expansion and new forms of sound production, result of the development of new unusual instrumental techniques compared to the traditional repertoire, thus, denominated like extended techniques, because they expand the interpretative possibilities from the twentieth century. During the present work, we selected three extended techniques, to present, discuss and perform their interpretations, Slide Glissandi, Vocalization and Open Tubing Technique. They were proposed because they minimally contemplate the works of the current repertoire of the instrument and aren’t discussed and used in contemporary books and methods, besides addressing aspects inherent to the problematization, as a consideration of the importance of research in musical performance, the complexity of musical interpretation and the diversity of concepts about the extended technique in general and its particularities in the trumpet.